Treatment for secondary hyperparathyroidism focusing on parathyroidectomy - Hiramitsu, Takahisa; Hasegawa, Yuki; Futamura, Kenta; Okada, Manabu; Goto, Norihiko; Narumi, Shunji; Watarai, Yoshihiko; Tominaga, Yoshihiro; Ichimori, Toshihiro (Frontiers in Endocrinology, 2023)
Secondary hyperparathyroidism (SHPT) is a major problem for patients with chronic kidney disease and can cause many complications, including osteodystrophy, fractures, and cardiovascular diseases. Treatment for SHPT has changed radically with the advent of calcimimetics; however, parathyroidectomy (PTx) remains one of the most important treatments. For successful PTx, removing all parathyroid glands (PTGs) without complications is essential to prevent persistent or recurrent SHPT. Preoperative imaging studies for the localization of PTGs, such as ultrasonography, computed tomography, and 99mTc-Sestamibi scintigraphy, and intraoperative evaluation methods to confirm the removal of all PTGs, including, intraoperative intact parathyroid hormone monitoring and frozen section diagnosis, are useful. Functional and anatomical preservation of the recurrent laryngeal nerves can be confirmed via intraoperative nerve monitoring. Total or subtotal PTx with or without transcervical thymectomy and autotransplantation can also be performed. Appropriate operative methods for PTx should be selected according to the patients’ need for kidney transplantation. In the case of persistent or recurrent SHPT after the initial PTx, localization of the causative PTGs with autotransplantation is challenging as causative PTGs can exist in the neck, mediastinum, or autotransplanted areas. Additionally, the efficacy and cost-effectiveness of calcimimetics and PTx are increasingly being discussed. In this review, medical and surgical treatments for SHPT are described.